A Technical Review on Advantages of Using EC BLDC Fans in Factory and Commercial Buildings. Issue 3 (1st May 2018) - Banu Rekha, B; Somasundaram, B; Ashok Kumar, L; Balekai, Pruthviraj
ABSTRACT: In modern industries and commercial buildings, optimization of heating ventilation and air conditioning (HVAC) systems is given greater focus as it is one of the major contributors for their energy consumption. Recent research studies highlight the advantages with respect to electrical parameters of energy efficient retrofits in air handling units (AHU) with an electronically commutated brushless direct current (EC BLDC) motor instead of an induction motor (IM). This article further provides technical review of inherent advantages such as reduction in noise and space, improvement in flexibility and reliability through data from real time implementation and experiments, along with simulation studies. Encouraging results from experimental data revealed that the EC BLDC motor driven fans can be deployed without noise attenuators and maintain noise levels below threshold standards. In addition, EC BLDC motor fans have a smaller form factor that makes the overall size of the AHU smaller and more compact. Simulation and real time data shows that accommodating AHUs inside the factory reduces loss in refrigeration as a result of solar heat gain when compared to conventional outdoor installation. This further reduces the maintenance and life time costs with improved reliability. Computational fluid dynamic (CFD) analysis performed in this work also shows lesser turbulence losses with the EC BLDC fan and promotes future study prospects on reduction in static pressure losses by redesigning the air path profile in an AHU.